Risk factors for falls in hospitalized adult patients: an integrative review - Isis Marques Severo; Miriam de Abreu Almeida; Ricardo Kuchenbecker; Débora Feijó Villas Boas Vieira; Michele Elisa Weschenfelder; Luciana Ramos Corrêa Pinto; Cristini Klein; Ana Paula de Oliveira Siqueira; Bruna Paulsen Panato (Revista da Escola de Enfermagem da USP, 2014)
Objective: Identifying risk factors for the occurrence of falls in hospitalized adult patients. Method: Integrative review carried out in the databases of LILACS, SciELO, MEDLINE and Web of Science, including articles published between 1989 and 2012. Results: Seventy-one articles were included in the final sample. Risk factors for falls presented in this review were related to patients (intrinsic), the hospital setting and the working process of health professionals, especially in nursing (extrinsic). Conclusion: The systematic screening of risk factors for falls was identified as a contributing factor to the reduction of this injury, helping the non-occurrence of this event that, despite being preventable, can have serious consequences including death.